Direct electrochemical synthesis of high-entropy alloys from metal oxides. (December 2017) - Sure, Jagadeesh; Vishnu, D. Sri Maha; Schwandt, Carsten
Graphical abstract: Schematic representation of synthesis of high-entropy alloy by electrochemical deoxidation of metal oxide mixture in a molten salt. Highlights: First-time synthesis of high-entropy alloys (HEA) by electrochemical deoxidation. Direct synthesis of refractory TiNbTaZr and TiNbTaZrHf from metal oxides in molten salt. Both HEAs comprise bcc solid-solution phases. Both HEAs are porous with low density but exhibit considerable strength. Abstract: It has been demonstrated for the first time that high-entropy alloys can be synthesised by electrochemical reduction in a molten salt. This was accomplished by means of an electrolytic cell in which pre-mixed solid metal oxides were subjected to cathodic polarisation in an electrolyte of molten CaCl2 salt at 1173 K, such that the equiatomic refractory alloys TiNbTaZr and TiNbTaZrHf were produced in a single-step alloying process. Structural investigations revealed that the TiNbTaZr alloy comprises two body-centred cubic phases while the TiNbTaZrHf alloy has one disordered body-centred cubic phase. Further examinations were carried out to assess the alloys' morphological and mechanical properties. These novel findings promise a straightforward, low-energy and cost-affordable electrometallurgical process for the production of high-entropy alloys for advanced structural applications.